ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN KANTOR CABANG PADA PT. BANK PEMBANGUNAN DAERAH JAWA TENGAH (PERIODE TAHUN 2012-2016) - Muhammad Rizki Nur Adi S; Eko Suyono; Wita Ramadhanti; Taufik Hidayat (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
Banking is one of the most important financial sub-systems and is having a great influence in the economy of a country, including Indonesia. To define the condition of how bad or how good the economy of Indonesia is, it can be reflected from its financial performance. According to the data from Infobank Research Bureau (2012) which has done the assessment to 120 banks in Indonesia, it shows that there are 83 banks with excellent predicate, 25 banks are well-predicated, 10 banks are respectable, and only 2 banks are predicated to be having poor preformance. Based on that fact, Financial Performance appeals to be studied in this research. This research aims to analyze the Analysis of Factors Affecting Financial Performance of branch offices of PT. Bank Pembangunan Daerah Central Java (2012-2016). The research population is all of PT. Bank Pembangunan Daerah Central Java’sbranch offices of 2012 to 2016 period. Purposive sampling technique is used as research sample. Number of samples that fit for this research are 36 branch offices with the total of 180 observations. Classical assumption test in this research includes normality, autocorrelation, multicollinearity, and heteroscedasticity test. Hypothesis testing uses the analysis of multiple-linear regression. According to the result of the analysis, the Loan to Deposit Ratio (LDR), BOPO, and Net Interest Margin (NIM) affect the financial performance. Meanwhile, Capital Adequacy Ratio CAR) and Non-Performing Loan (NPL) has no effect towards the financial performance of Branch Offices of PT. Bank Pembangunan Daerah Central Java. It is also concluded that financial distress of PT. Bank Pembangunan Daerah Central Java’s branch offices is in good average.